Contributions of social representation theory to Ibero-American psychology: a documentary analysis in Scielo - Barbosa, Ana Clotilde Coutinho (2025)
The Theory of Social Representations, proposed by Serge Moscovici in 1961, is a milestone in understanding social thought. This study analyzed 285 abstracts from Ibero-American psychology journals available in the SciELO database, processed with the IRAMuTeQ software. Five thematic classes were identified within two main axes: the first addresses methodological aspects, Class 1 (analysis techniques and software) and Class 2 (sample characteristics); the second concerns the development of studies on Social Representations, Class 3 (family-related themes), Class 4 (health themes), and Class 5 (contents of Moscovici’s Theory). It was found that IRAMuTeQ structured classes consistent with the abstracts and highlighted the predominance of Moscovici’s theoretical